Some effect of environmental noise on the academic attainment of students attending regular secondary schools in Ibadan metropolis (2015)
The study examined the effect of environmental noise on the academic attainment of some secondary school students in order to determine the relationship between the two variables. 500 randomly selected secondary school students from four purposively selected schools of 125 each formed the participants for the study who were assessed with the use of Sound Pure Tone Audiometres (PTA), and a self- developed Environmental Noise on Academic Attainment Scale (ENASS) with a reliability coefficient of .85 Alpha. The results of the study through the use of some level meter (SLM) showed that the external noise of the participating schools exceeded the standard of 35dB set by the WHO, with a significant difference in the sound level of schools located in a noisy environment and those of noise- free environment. The hearing level of participants from a noisy environment was found to differ significantly from the hearing level of participants from a noise- free environment (5.445> 1.96; = P< 0.05), while the educational attainment of participants from schools in a noisy environment and participants from noise- free schools also differed significantly (5.61> 1.96; = P< 0.05). It was therefore suggested that government should enforce the public laws on school- site, noise- control and hearing conservation. Also, there should be strict compliance to the global standard in that generated noise level in schools must not exceed the standard of 35db set by the WHO, as noise has been found to have a deleterious effect on the academic attainment of school children.